ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA - Rijal Arslan (Politeknik Negeri Ambon, 2022)
The purpose of this research is to study and analyze the influences of The Quality of Service on the Costumer Satisfaction of PT Bank Syariah Indonesia. The Quality of Service in this research uses five variables, which are: tangible, reliability, responsiveness, assurance and empathy have relationship with Customer Satisfaction. In this research, Multiple regression of technical analysis is applied. To test the impact, F test is applied and to test the partial influence, t test is applied at significant level 0,05. The number of samples used for this analysis are 100 customers of PT Bank Syariah Indonesia. The result of this research also simultaneously that the Quality of Service (e.g., tangibles, reliability, responsiveness, assurance and empathy) has a positive effect and significant to the Customer Satisfaction. While partially only responsiveness and assurance variables has an effect with customer satisfaction, while tangibles, reliability and empathy does not has an effect with customer satisfaction.